Study on interface structure and thermal conductivity regulation of Cu–In composite thermal interface materials - Jie Zhang; Nan Wu; Hong Guo; Zhongnan Xie; Mingmei Sun; Hui Yang; Ximin Zhang; Yulin Liu; Xinbo He (Journal of Materials Research and Technology)
In foil has excellent heat dissipation performance as a commercially available thermal interface material for high power devices. In order to improve the heat transfer performance of In-based thermal interface materials, a composite thermal interface material with In as the matrix and Cu as the reinforcement was prepared in this research by hot press sintering. The Cu–In composite material's characteristic interfacial structure was examined through the use of transmission electron microscopy. Theoretical models were employed to determine the thermal conduction patterns across various CuIn phase interfaces. By fine-tuning the parameters of the hot press sintering process, we were able to regulate the CuIn phase interface layer's morphology. Results indicate that the Cu–In interface is bonded through a reactive interface, leading to the formation of the CuIn phase that is tightly atomically bonded with both In and Cu. The CuIn phase, when continuous, exhibits higher interfacial thermal conductivity as its thickness decreases. Practical fabrication considerations show that the CuIn phase interface transitions from discontinuous to continuous at a thickness of ∼0.91 μm. Therefore, a continuous CuIn phase interface layer of about 0.91 μm thick yields the highest thermal conductivity, reaching 122.25 Wm−1K−1, which is 1.4 times greater than that of pure In. This research presents innovative choices and strategic directions for advancing the field of high-thermal-conductivity interfacial materials.